(untitled) (Collection of scientific works «Modern structures of metal and wood», 2024)
The main methods of mechanical testing of composite materials include: determination of material strength under tension, bending, torsion, shock loads, compression, etc. This article presents the preparatory stage of conducting experimental studies on determining the bending strength of structural elements made of ABS plastic, manufactured with the help of 3D printing. As a result 2 series of experimental samples are indicated, which differ in the shape of the cross section (specimens of 1 st series have rectangular section, samples of 2 nd series have T-shaped section), appropriate dimensions and a test scheme are established in accordance with the requirements of regulatory documents. The percentage of filling of the internal cavity of the experimental elements with polymer material was determined, namely 10%, 50% and 100%. The algorithm of preparation and direct execution of the planned tests under the action of a static short- term load is described. The predicted schemes and criteria for the destruction of the samples, as well as the conditions for stopping the tests, are given.